The use of shells as tools by hunters-gatherers in the Beagle Channel (Tierra del Fuego, South America): an ethnoarchaeological experiment - Malainey, Mary (2014)
This paper presents the results of the analysis of lipid residues extracted from two Aulacomya atra shells and a single Mytilus edulis shell found in the hunter-fisher-gatherer site of Lanashuaia II, a shell midden located on the Beagle Channel (Tierra del Fuego, Argentina). According to existing ethnographic information, the shells could have been used as receptacles (like spoons) or knives by the Yamana people that inhabited the region in the historical period (nineteenth and twentieth centuries). Yamana society is the final moment of a long history of hunter-fisher-gatherer societies present in the Beagle Channel and the rest of Fuegian Channels and islands. Higher concentrations of lipid residues were recovered from both A. atra shells than from the sedimentary control sample analyzed. This is consistent with existing accounts that these types of shells were used as containers to cook or melt fat-rich foods. The composition of lipids extracted from archaeological shell was significantly different from the degraded reference cooking residues prepared from modern A. atra shells.